REAL-TIME PCR OPTIMIZATION FOR LISTERIA MONOCYTOGENES GENOME DETECTION - G. S. Skitovich; N. B. Shadrova; O. V. Pruntova; K. V. Serova (Ветеринария сегодня)
Listeria monocytogenes is one of the major food contaminants causing the illness, called Listeriosis. Listeriosis incidence is much less, than the number salmonellosis and campylobacteriosis cases, but the clinical disease is significantly more severe and has a higher mortality. That’s why the development of species-specific PCR techniques to detect L. monocytogenes genome is a topical task. L. monocytogenes bacteria genome detection technique using real-time polymerase chain reaction (qRT-PCR) was improved. The amplification target was a highly specific and suitable for qualification of all strains iap gen, coding L. monocytogenes р60 surface protein. Optimum magnesium concentration (6 mM) and primer annealing temperature (57 °С) were selected. The sensitivity and specificity of the technique were identified. Detection threshold was 120 target molecules. The results obtained demonstrate that optimized qRT-PCR version, based on iap gen amplification, enables to detect L. monocytogenes in animal product and food samples. Optimized qRT-PCR-based screening tests ensure rapid and reliable results.